Estudo dos sistemas de impermeabilização: patologias, prevenções e correções - análise de casos - Righi, Geovane Venturini (2010)
The waterproofing is a very important step in the civil construction, but it has been relegated, mostly by cost containment and misinformation, resulting in the manifestation of waterproofing pathologies. Repair costs of these pathologies can be up to fifteen times higher than if it were running on the course of the work. This study presents a multiple cases studies of waterproofing pathologies, with suggestions of corrections and indications on how to prevent such pathologies. To better illustrate the subject, it was accomplished an inspection of the main types of materials used in the waterproofing process, as well as the applied techniques, main cares that should be considered in the execution and indispensable constructive details in the process.